Estudo comparativo entre a aplicação do novo regime diferenciado de contratações (RDC) e a lei de licitações no âmbito da Universidade Federal De São Carlos - UFSCar - Vasco, Elicio Pedro Cantero (2016)
One of the most important activities and that is increasingly gaining importance in recent years, among the various activities undertaken by the public authorities is on the shopping area. The bidding is an administrative procedure in which aims to select, according to predetermined objective criteria, the most advantageous hiring proposal to the government. In this process should be ensured broad participation of stakeholders, as well as equal treatment, always permeated with the legal requirements. Law n. 8.666 / 93, the General Law of Tenders and Administrative Contracts, establishes all the legal system for public procurement. The Differentiated Regime Hiring - DRC - is permeated by several goals, innovative in relation to the rules established by Law 8.666 / 93. UFSCar has adopted this regiment in their hiring process works and engineering services since 2013. The main objective of this work is to promote a comparative study between the Differentiated Regime Signings, DRC and Competition mode, governed by Law n. 8666/93 regarding the efficient procurement of works and engineering services within the UFSCar. For that was used in the methodological procedure descriptive and exploratory research through two approaches: quantitative and qualitative. The first approach corresponded to the comparative analysis, obtained by hiring historical data from the modality competition, the years 2011, 2012 and 2013, and DRC mode the years 2013, 2014 and 2015, coming from the reports of the Purchasing Department - Decom / UFSCar and Comprasgovernamental. They were established some indicators whose purpose was to measure the efficiency of the new procurement regime in relation to the mode set by competition. The qualitative approach was used to analyze the perceptions of representatives of the units that are closely linked to the bidding process under the UFSCar. The main results show that there are many perspectives introduced by the DRC, of which some have already been implemented in the bidding process for procurement of works and engineering services in this federal public education institution. Among the challenges are the various requirements, legal, technical, economic, financial and regularity with which the government by constitutional and legal provisions, is obliged to demand.. It was found that there are many drivers listed in DRC of which is an instrument capable of providing more agile, economical and efficient procurement ways, especially compared to the competition mode. On the other hand, being a relatively new law, the DRC still lacks depth studies that aim to remedy many of the doubts in its various devices and mechanisms. These factors can be mitigated through exchange of experiences with other organizations that also use the DRC in order to refine and improve its use at the university.